The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1002/qua.21685
|View full text |Cite
|
Sign up to set email alerts
|

MP2, DFT‐D, and PCM study of the HMB–TCNE complex: Thermodynamics, electric properties, and solvent effects

Abstract: Geometry, thermodynamic, and electric properties of the -EDA complex between hexamethylbenzene (HMB) and tetracyanoethylene (TCNE) are investigated at the MP2/6-31G* and, partly, DFT-D/6-31G* levels. Solvent effects on the properties are evaluated using the PCM model. Fully optimized HMB-TCNE geometry in gas phase is a stacking complex with an interplanar distance 2.87 ϫ 10 Ϫ10 m and the corresponding BSSE corrected interaction energy is Ϫ51.3 kJ mol Ϫ1. As expected, the interplanar distance is much shorter in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…Some observed discrepancies (e.g., in reaction enthalpy, dipole moment, IR modes, etc.) between theoretical and experimental data for HMB-TCNE [5,6,9] can be partly explained by the overestimated interplanar distance in the complex obtained at the HF and DFT levels. As it follows from previous studies on stacking complexes [12][13][14], for proper description of the dispersion interactions in these complexes, the proper inclusion of the electron correlation (EC) effects seems to be crucial.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“…Some observed discrepancies (e.g., in reaction enthalpy, dipole moment, IR modes, etc.) between theoretical and experimental data for HMB-TCNE [5,6,9] can be partly explained by the overestimated interplanar distance in the complex obtained at the HF and DFT levels. As it follows from previous studies on stacking complexes [12][13][14], for proper description of the dispersion interactions in these complexes, the proper inclusion of the electron correlation (EC) effects seems to be crucial.…”
Section: Introductionmentioning
confidence: 74%
“…This rather important finding might be connected with donor-acceptor interplanar distances, which is, consequently, related to the amount of transferred electronic charge from methylated benzenes to TCNE acceptor. This point has been discussed in detail in experimental [4,5] and in our previous theoretical article [9]. In our preceding article [9], we have also shown that because of the solvent effects, the interplanar distance HMB-TCNE is enlarged by 0.2-0.3 ϫ 10 Ϫ10 m compared with that calculated in gas phase.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…with values typical for hydrogen bonds [20]. The strong binding site of the molecule is an alcohol group (-OH) which provides the hydrogen bonds of the same strength (at around 1.529-1.552 Å) that is even stronger then could be formed between water molecules (1.537 -1.834 Å).…”
Section: Figure 5 : Configurations Of Imide Head Group With Twelve Wamentioning
confidence: 99%